Sonochemical conversion of CO2 into hydrocarbons: The Sabatier reaction at ambient conditions - Md Hujjatul Islam; Odne S. Burheim; Jean-Yves Hihn; Bruno.G. Pollet (Ultrasonics Sonochemistry, 2021)
In this study, we investigated an alternative method for the chemical CO2 reduction reaction in which power ultrasound (488 kHz ultrasonic plate transducer) was applied to CO2-saturated (up to 3%) pure water, NaCl and synthetic seawater solutions. Under ultrasonic conditions, the converted CO2 products were found to be mainly CH4, C2H4 and C2H6 including large amount of CO which was subsequently converted into CH4. We have found that introducing molecular H2 plays a crucial role in the CO2 conversion process and that increasing hydrogen concentration increased the yields of hydrocarbons. However, it was observed that at higher hydrogen concentrations, the overall conversion decreased since hydrogen, a diatomic gas, is known to decrease cavitational activity in liquids. It was also found that 1.0 M NaCl solutions saturated with 2% CO2 + 98% H2 led to maximum hydrocarbon yields (close to 5%) and increasing the salt concentrations further decreased the yield of hydrocarbons due to the combined physical and chemical effects of ultrasound. It was shown that CO2 present in a synthetic industrial flue gas (86.74% N2, 13% CO2, 0.2% O2 and 600 ppm of CO) could be converted into hydrocarbons through this method by diluting the flue gas with hydrogen. Moreover, it was observed that in addition to pure water, synthetic seawater can also be used as an ultrasonicating media for the sonochemical process where the presence of NaCl improves the yields of hydrocarbons by ca. 40%. We have also shown that by using low frequency high-power ultrasound in the absence of catalysts, it is possible to carry out the conversion process at ambient conditions i.e., at room temperature and pressure. We are postulating that each cavitation bubble formed during ultrasonication act as a “micro-reactor” where the so-called Sabatier reaction -CO2+4H2→UltrasonicationCH4+2H2O - takes place upon collapse of the bubble. We are naming this novel approach as the “Islam-Pollet-Hihn process”.